The business of UX writing - Ben-David, Yael (Book Apart (Series), 2022)
UX writing is good for business, while also playing a critical role in delivering a top-notch user experience. Standing at this pivotal intersection between business goals and user needs is an awesome place to be—as long as we have the mindset, tools, and collaborators to make the most of it. Through case studies, frameworks, and historical context, Yael Ben-David offers savvy and practical guidance to ensure our digital products support the user and the business—plus writers and designers!—all at once.